Pengaruh Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Pegawai - Nurul Annisa Haedar. Af; Tenri Sayu; Burhanuddin Burhanuddin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to determine whether there is an influence of the physical and non-physical work environments on employee job satisfaction at Dr. Tadjuddin Chalid Central General Hospital Makassar. This research is quantitative in nature with a descriptive approach and is population-based. The sample for this study consists of 78 nurses from the inpatient ward of Dr. Tadjuddin Chalid Central General Hospital Makassar. Hypothesis testing in this study utilizes multiple linear regression analysis and yields the following results: Based on the hypothesis testing results using multiple linear regression analysis, it is indicated that both the physical and non-physical work environment variables simultaneously affect employee job satisfaction at Dr. Tadjuddin Chalid Central General Hospital Makassar. The hypothesis testing results also demonstrate that the physical work environment partially affects employee job satisfaction at Dr. Tadjuddin Chalid Central General Hospital Makassar, and the non-physical work environment partially affects employee job satisfaction at Dr. Tadjuddin Chalid Central General Hospital Makassar.